Antibacterial Effectiveness Test of Lemongrass Leaf (Cymbopogon Citratus) Boiled Water In Decreasing The Number of Escherichia Coli Bacterial Colonies - Kisi Rahmadevy; Syarifah Miftahul El Jannah T; Nur Alfi Syahri; Endang Uji Wahyuni; Sri Ani (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
The presence of disease can be caused by a microorganism (virus, bacteria, fungus and parasite), and the environment that can infect a person either directly or through intermediaries. Environmental components such as air, water, food, and others are the natural transfer paths of disease. So that humans must maintain personal hygiene, the environment and equipment that is often used such as cutlery to avoid the threat of pathogenic microorganisms. Contamination in the washing process of cutlery by water containing Escherichia coli bacteria will damage the quality of food and cause diarrhea. One of the efforts to reduce the number of germs is to disinfect using chemicals such as chlorine. However, the use of chemicals actually has a negative impact on health and the environment, we need alternatives that do not cause pollution and are safe for humans such as the use of natural materials. One of them is lemon grass which can be used as an antibacterial. This experimental study aimed to determine the antibacterial effectiveness of lemongrass leaves with concentrations of 10%, 15%, 20% and 25% in reducing the number of Escherichia coli bacterial colonies after 5 minutes, 10 minutes and 15 minutes of contact, using the spread plate method with EMBA media. The results showed a decrease in the number of Escherichia coli bacterial colonies after treatment using boiled water from lemongrass leaves from a concentration of 10% after 5 minutes of contact. Based on the ANOVA analysis, it was found that p-value 0.05 there was a significant difference in each variation of concentration and contact time. The boiled water of lemongrass leaves with the highest level of effectiveness is in concentration of 25% with a contact time of 15 minutes.